2018
DOI: 10.1016/j.nicl.2017.10.030
|View full text |Cite
|
Sign up to set email alerts
|

MRI features predict p53 status in lower-grade gliomas via a machine-learning approach

Abstract: BackgroundP53 mutation status is a pivotal biomarker for gliomas. Here, we developed a machine-learning model to predict p53 status in lower-grade gliomas based on radiomic features extracted from conventional magnetic resonance (MR) images.MethodsPreoperative MR images were retrospectively obtained from 272 patients with primary grade II/III gliomas. The patients were randomly allocated in a 2:1 ratio to a training (n = 180) or validation (n = 92) set. A total of 431 radiomic features were extracted from each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 45 publications
3
58
0
1
Order By: Relevance
“…Despite the considerable data heterogeneity, they successfully predicted 1p/19q codeletion and discriminated LGGs on the basis of 1p/19q-codeletion status with an accuracy of 87% by extracting the top 39 texture features, mostly from CE-MR imaging and T2WI. Li et al [56][57][58] accurately predicted alpha thalassemia mentalretardation syndrome, epidermal growth factor receptor, and p53 status in patients with LGG on T2WI. In general, the secondorder TA on CE-MR imaging and FLAIR images mostly contributed to the high accuracy for predicting genomic status.…”
Section: Glioma Radiogenomicsmentioning
confidence: 99%
“…Despite the considerable data heterogeneity, they successfully predicted 1p/19q codeletion and discriminated LGGs on the basis of 1p/19q-codeletion status with an accuracy of 87% by extracting the top 39 texture features, mostly from CE-MR imaging and T2WI. Li et al [56][57][58] accurately predicted alpha thalassemia mentalretardation syndrome, epidermal growth factor receptor, and p53 status in patients with LGG on T2WI. In general, the secondorder TA on CE-MR imaging and FLAIR images mostly contributed to the high accuracy for predicting genomic status.…”
Section: Glioma Radiogenomicsmentioning
confidence: 99%
“…1 The newly merged field of machine learning further allows the specifics of radiomics to be integrated into ancillary diagnostic methods. Previous studies have added the benefits of machine learning to the glioma World Health Organization grading classification, 15 gene mutation, 16,17 and survival. 18 Only a few studies have attempted machine learning for the differential diagnosis between recurrence and TRE.…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics is an emerging field of research that encompasses the extraction of quantitative features from biomedical images that may reflect underlying pathophysiology (22). It has been shown to be a useful tool in the analysis of chest CT scans (23,24) and MR images (25,26). Studies have shown that radiomic features are often useful predictors of, or are associated with, known hallmarks of disease, although they have not been used extensively in the MS literature.…”
Section: Introductionmentioning
confidence: 99%